Intelligent vehicle black box using IoT - Anil Kumar, M; Venkata Suman, M; Misra, Yogesh; Geetha Pratyusha, M (International Journal of Engineering and Technology, 2018)
Millions of people die due to the accidents.The main purpose of this paper is to provide vehicle safety and a solution that automatically alert the driver to be cautious. In this paper we continuously monitor the vehicle performance using sensors and the behavior of driver with the use of IoT Technology.The Vehicle black box receives the information from various sensors like the breath analyzer, acceleration and the distance of surrounding vehicles along with push and panic button. When the driver alcohol consumption reaches maximum limit, the messages are sent to emergency contacts. If the accident occurs, by using GSM and GPS the vehicle location is traced and the information is sent to local hospital and police.With the IoT Technology, this location is always traced in the cloud platform service.The push and panic button is used to alert the 24/7 Governance to call out for emergency help.